Protein-binding affinity of leucaena condensed tannins of differing molecular weights - Huang, X.D.; Liang, J.B.; Tan, H.Y.; Yahya, R.; Long, R.; Ho, Y.W. (2011)
Depending on their source, concentration, chemical structure, and molecular weight, condensed tannins (CTs) form insoluble complexes with protein, which could lead to ruminal bypass protein, benefiting animal production. In this study, CTs from Leuceana leucocephala hybrid were fractionated into five fractions by a size exclusion chromatography procedure. The molecular weights of the CT fractions were determined using Q-TOF LC-MS, and the protein-binding affinities of the respective CT fractions were determined using a protein precipitation assay with bovine serum albumin (BSA) as the standard protein. The calculated number-average molecular weights (M n) were 1348.6, 857.1, 730.1, 726.0, and 497.1, and b values (the b value represents the CT quantity that is needed to bind half of the maximum precipitable BSA) of the different molecular weight fractions were 0.381, 0.510, 0.580, 0.636, and 0.780 for fractions 1, 2, 3, 4, and 5, respectively. The results indicated that, in general, CTs of higher molecular weight fractions have stronger protein-binding affinity than those of lower molecular weights. However, the number of hydroxyl units within the structure of CT polymers also affects the protein-binding affinity.